Silence, gender and metamorphosis in Joanna Walsh's 'Worlds from the Word's End'. Issue 1 (1st June 2021) - Fagan, Paul
This article explores paradoxical silence as a strategy of contemporary feminist short story writing in Joanna Walsh's 'Worlds from the Word's End' (2017). To draw out the story's engagements with writing women's agency beyond the binaries of embodiment and disembodiment, passivity and activity, inner and outer life, it reads Walsh's text at the nexus of three interrelated traditions. First, it situates the story within a genealogy of women's 'non-writing', which develops new aesthetic strategies through the short story form for both writing and reading the silences of women. Secondly, it explores the significance of women's speech loss in Ovid's The Metamorphoses to the transformative drive of Walsh's poetics of silence, with a specific focus on the figure of Echo. Thirdly, it places Walsh's epistolary short story into conversation with philosophical debates about the distinct silences of plenitude and vacuum, transcendence and immanence, the human and the nonhuman, by reading it comparatively with Hugo von Hofmannsthal's 'Ein Brief'. In conclusion, it is argued that 'Worlds from the Word's End' ironizes the Ovidian topos of the silent figure who nevertheless speaks her desires in order to trouble the binaries that regulate strategies of voluntary silence in the feminist short story.